Clayey Ceramic Incorporated With Powder from the Sintering Plant of a Steel-Making Industry - M. M. Ribeiro; S. N. Monteiro; C. M. F. Vieira (The Minerals, Metals and Materials Society, 2011)
"This work has as its objective to evaluate the effect of incorporation of the powder waste retained in the eletrostatic precipitator of the sintering stage from an integrated steel making plant on the physical and mechanical properties of a red ceramic. Formulations were prepared with incorporation of the waste in amounts up to 20 wt.% into a kaolinitic clay. Rectangular specimens were prepared by uniaxial mold-press at 20 MPa and then fired at 750, 900 and 1050°C. The evaluated physical and mechanical properties were: linear shrinkage, water absorption and flexural rupture strength. The results showed that the waste has a potential to be used into red ceramics. The incorporation of the waste enhanced the properties of the ceramic, decreasing the water absorption and increasing the mechanical strength at all investigated temperatures.IntroductionThe sintering stage of an integrated steel-making plant is dedicated to the agglomeration of a mixture of iron ore, coke or coal, fluxes and water [1]. It is a common practice in this stage to use of solid wastes with great amounts of iron in the form of sludge and powder. One of the atmospheric pollutants generated during the sintering process is the particulate material, which is normally retained in an equipment denote as electrostatic precipitator. This equipment retains very small particulates, present in the gaseous emissions by application of an electrical potential difference in between the plates that the fluid is forced to go through. [2]."